2019
DOI: 10.29333/iji.2019.12121a
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Students in Reading the Quran: A Reflective-Critical Treatment through Action Research

Abstract: To improve the skill in reading the Quran correctly, students need to be given skills in learning to read the Quran quickly and effectively so that they can know the Arabic alphabet well, pronounce it correctly, understand the elocution of reading, and understand its meaning well. The action research report presented in this journal article exemplifies the collaborative teamwork involved in making the reflective-critical steps to improve the students' skill from their initial state of being unable to read the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 11 publications
0
18
0
5
Order By: Relevance
“…Pandai membaca maupun menulis bahkan memahami al-Qur'an bagi setiap muslim merupakan kewajiban (Ritonga, 2016), (Supriyadi & Julia, 2019), (Noh & Huda, 2020 (Novita, 2019), (Tisnelly et al, 2020), (Nurhattati et al, 2020).…”
Section: A Pendahuluanunclassified
“…Pandai membaca maupun menulis bahkan memahami al-Qur'an bagi setiap muslim merupakan kewajiban (Ritonga, 2016), (Supriyadi & Julia, 2019), (Noh & Huda, 2020 (Novita, 2019), (Tisnelly et al, 2020), (Nurhattati et al, 2020).…”
Section: A Pendahuluanunclassified
“…This research was conducted using an action research design, which is currently a popular design used in pedagogic research (Edwards-Groves & Kemmis, 2016;Somekh & Zeichner, 2009;Supriyadi & Julia, 2019;Zuber-Skerritt, 2018). The most distinctive aspect of this design is that improvements can be made by the problem solver (Bozkuş & Bayrak, 2019;Greenwood & Levin, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results of previous research, there was found many students in several Islamic universities in Indonesia with low Qur'an reading skills (Alhamuddin, Hamdani, Tandika, & Adwiyah, 2018;Otaya, Anwar, & Husain, 2019). There was also found that many students in several high schools were not yet skilled in reading the Qur'an correctly and smoothly (Supriyadi & Julia, 2019).…”
Section: Introductionmentioning
confidence: 99%